Biology of Pellino1: a potential therapeutic target for inflammation in diseases and cancers - Yan, Lili; Cui, Yueran; Feng, Juan (Frontiers in Immunology, 2023)
Pellino1 (Peli1) is a highly conserved E3 Ub ligase that exerts its biological functions by mediating target protein ubiquitination. Extensive evidence has demonstrated the crucial role of Peli1 in regulating inflammation by modulating various receptor signaling pathways, including interleukin-1 receptors, Toll-like receptors, nuclear factor−κB, mitogen-activated protein kinase, and phosphoinositide 3-kinase /AKT pathways. Peli1 has been implicated in the development of several diseases by influencing inflammation, apoptosis, necrosis, pyroptosis, autophagy, DNA damage repair, and glycolysis. Peli1 is a risk factor for most cancers, including breast cancer, lung cancer, and lymphoma. Conversely, Peli1 protects against herpes simplex virus infection, systemic lupus erythematosus, esophageal cancer, and toxic epidermolysis bullosa. Therefore, Peli1 is a potential therapeutic target that warrants further investigation. This comprehensive review summarizes the target proteins of Peli1, delineates their involvement in major signaling pathways and biological processes, explores their role in diseases, and discusses the potential clinical applications of Peli1-targeted therapy, highlighting the therapeutic prospects of Peli1 in various diseases.